2013
DOI: 10.1590/s0102-86502013000500006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of three different biomaterials as scaffolds for canine mesenchymal stem cells

Abstract: PURPOSE:To evaluate in vitro ability the of three different biomaterials -purified hydroxyapatite, demineralized bone matrix and castor oil-based polyurethane -as biocompatible 3D scaffolds for canine bone marrow mesenchymal stem cell (MSC) intending bone tissue engineering. METHODS:MSCs were isolated from canine bone marrow, characterized and cultivated for seven days with the biomaterials.Cell proliferation and adhesion to the biomaterial surface were evaluated by scanning electron microscopy while different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
2
7
0
1
Order By: Relevance
“…Thus, combining BMSCs with DBM should have a synergistic effect on the treatment of bone defects. Moreover, when DBM, a resorbable biomaterial, is seeded with BMSCs, it can promote the adhesion and proliferation of MSCs [31]. In the present study, when the bone defect areas in the Ad-BMP2-bFGF-GFP group were filled with mature trabecular bone, a large number of bone cells were visible on the surface by 12 weeks after the operation.…”
Section: Discussionsupporting
confidence: 46%
“…Thus, combining BMSCs with DBM should have a synergistic effect on the treatment of bone defects. Moreover, when DBM, a resorbable biomaterial, is seeded with BMSCs, it can promote the adhesion and proliferation of MSCs [31]. In the present study, when the bone defect areas in the Ad-BMP2-bFGF-GFP group were filled with mature trabecular bone, a large number of bone cells were visible on the surface by 12 weeks after the operation.…”
Section: Discussionsupporting
confidence: 46%
“…This study verifies that granular hydroxyapatite scaffold fulfills the criteria of an optimal scaffold for bone tissue engineering as it promoted cell adhesion and induced osteogenesis of MC3T3-E1, DPSC and SHED. This is in agreement with Pereira-Junior et al [ 37 ] who assessed the efficiency of the granular hydroxyapatite scaffold using BMSC and they proved that the gHA scaffold supports the adhesion and the differentiation of BMSC. The limitation of this study is that the osteogenic differentiation was not confirmed by, for example, Alizarin red staining, use other osteogenic specific marker such as Osterix, osteocalcin, BMP, RUNX2 etc., which will be addressed in future study.…”
Section: Discussionsupporting
confidence: 92%
“…In a separate study, BMSCs even substitute for neural progenitor cells (NPCs) in restorative therapy for stroke [3]. BMSCs can differentiate into osteoblasts, which makes them a suitable cell type in bone repair and tissue engineering [4,5,6,7]. The osteogenic differentiation of BMSCs can be regulated by multiple signaling molecules and transcriptional regulators, and how to enhance the osteogenic differentiation of BMSCs has gained increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%